Women Entrepreneurs Empowerment: A Literature Review - Sinaga, Klemensia Erna Christina (Journal of Economics and Business (JECOMBI), 2024)
This study explores the role of women’s economic empowerment through entrepreneurship as a transformative force for achieving sustainable development. Entrepreneurship provides women with opportunities to generate wealth, create jobs, and contribute to their communities while also challenging societal norms and enhancing their autonomy. Despite these benefits, women entrepreneurs face significant barriers, including limited access to education, financial resources, and networks, compounded by socio-cultural norms and systemic inequalities, particularly in developing countries like Indonesia. Using a narrative literature review, this research highlights the challenges and opportunities for women entrepreneurs, emphasizing the need for targeted policies, improved access to resources, and gender-sensitive interventions. The findings underscore the transformative impact of entrepreneurship on women’s empowerment, advocating for more inclusive and sustainable approaches to address gender disparities in economic participation.